"F(s)=\\int\\limits_0^\\infty e^{-t\\cdot s}\\cdot f(t)\\,dt=\\\\\n=\\int\\limits_0^\\infty e^{-t\\cdot s}\\cdot t^2\\cdot\\sinh(at)\\,dt=\\\\\n=\\int\\limits_0^\\infty e^{-t\\cdot s}\\cdot t^2\\cdot\\frac{e^{at}-e^{-at}}{2}\\,dt=\\\\\n=\\frac{1}{2}\\cdot\\int\\limits_0^\\infty t^2\\cdot(e^{(-s+a)t}-e^{(-s-a)t})\\,dt=\\\\\n=\\frac{1}{2}\\cdot\\int\\limits_0^\\infty t^2\\cdot e^{-(s-a)t}\\,dt-\\frac{1}{2}\\cdot\\int\\limits_0^\\infty t^2\\cdot e^{-(s+a)t}\\,dt=\\\\\n=\\frac{1}{2}\\cdot \\frac{1}{(s-a)^3}\\cdot\\varGamma(3) - \\frac{1}{2}\\cdot \\frac{1}{(s+a)^3}\\cdot\\varGamma(3)=\\\\\n=\\{\\varGamma(3)=(3-1)!=2\\}=\\frac{1}{(s-a)^3}-\\frac{1}{(s+a)^3};"
Comments
Leave a comment